Предмет: Математика, автор: prostla64

Упростить выражения .​

Приложения:

Ответы

Автор ответа: 22larchik50
1

Пошаговое объяснение:

1) {2}^{ - 1}  \times  {64}^{ \frac{2}{3} }  =  {2}^{ - 1}  \times  {2}^{4}  =  {2}^{ - 1 + 4} =  {2}^{3}   = 8

2) {3}^{ - 2}  \times  {81}^{ \frac{1}{4} }  =  {3}^{ - 2} ( {3}^{4} )^{ \frac{1}{4} }  = ( {3}^{4} )^{ \frac{1}{4} }  =  {3}^{ - 2}  \times 3 =  {3}^{ - 1}  =  \frac{1}{3}

3) {100}^{ -  \frac{1}{2} }  =  \frac{1}{ {100}^{ { \frac{1}{2} }^{} } } =  \frac{1}{( {10}^{2})^{ \frac{1}{2} }  }  =  {10}^{2 \times  \frac{1}{2} }  =  {10}^{1}  =  \frac{1}{10}

4) {(27 \times 125)}^{ \frac{1}{3} }  = {3375}^{ \frac{1}{3} }  = ( {15}^{3} )^{ \frac{1}{3} }  =  {15^{1} }  = 15

5)( \frac{1}{36}  \times 0.04)^{ \frac{1}{2} }  = ( \frac{1}{36}  \times  \frac{1}{25} ) ^{2 \frac{1}{2} }  =  \frac{1}{36 \times 25}  = ( \frac{1}{900} )^{ \frac{1}{2} }  =  \sqrt{ \frac{1}{900} }  =  \frac{1}{30}

6)( \frac{1}{16}  \times  {81}^{ - 2})^{ -  \frac{1}{4} }  = ( \frac{1}{16}  \times  \frac{1}{ {81}^{2} } )^{ -  \frac{1}{4} }  = ( \frac{1}{ {16 \times 81}^{2} } ) ^{ -  \frac{1}{4} }  = ( {16 \times 81}^{2} )^{ \frac{1}{4} }  =  \sqrt[4]{ {16 \times 81}^{2} }  =  \sqrt[4]{ {324}^{2} }  =  \sqrt{324}  = 18

Похожие вопросы
Предмет: Химия, автор: макс1038